The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/jhq.0000000000000277
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Association Between the Quality of HIV Care in Nursing Homes and Hospitalization

Abstract: Persons living with HIV/AIDS (PLWH) are living long enough to need age-related and HIV-related nursing home (NH) care. Nursing home quality of care has been associated with risk for hospitalization, but it is unknown if quality of HIV care in NHs affects hospitalization in this population. We assessed HIV care quality with four national measures adapted for the NH setting. We applied the measures to 2011–2013 Medicare claims linked to Minimum Data Set assessments of resident health, prescription dispensing dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Despite the surge in older PLWH, little data has thus far been collected regarding long‐term care options for these patients. A recent study by Olivieri‐Mui et al., 2021 found that of the 1246 PLWH studied who were admitted to nursing homes, nearly 74% were male, relatively young (mean age of 59.9, SD = 12.02), and were mostly entitled to Medicare due to disability (69.9%). A 2017 study by Naudet examined some of the challenges and obstacles that older PLWH faced when seeking admission to nursing or long‐term care facilities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the surge in older PLWH, little data has thus far been collected regarding long‐term care options for these patients. A recent study by Olivieri‐Mui et al., 2021 found that of the 1246 PLWH studied who were admitted to nursing homes, nearly 74% were male, relatively young (mean age of 59.9, SD = 12.02), and were mostly entitled to Medicare due to disability (69.9%). A 2017 study by Naudet examined some of the challenges and obstacles that older PLWH faced when seeking admission to nursing or long‐term care facilities.…”
Section: Methodsmentioning
confidence: 99%
“…As the number of new PLWH enter long‐term care facilities and nursing homes increases, steps should be taken to ensure that the staff caring for these patients are competent in meeting the unique needs of older (or even younger) PLWH (Justice & Akgün, 2019; Olivieri‐Mui, 2021). Multidisciplinary health care teams are vital to deal with the complex clinical and psychosocial issues facing this population.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation